Therapeutic efficacy of platinum/etoposide regimens in the treatment of advanced poorly differentiated neuroendocrine carcinomas of the lung: A retrospective analysis - Puliafito, Ivana; Chillari, Federico; Russo, Alessandro; Cantale, Ornella; Sciacca, Dorotea; Castorina, Luigi; Colarossi, Cristina; Franchina, Tindara; Vitale, Maria Paola; Ricciardi, Giuseppina Rosaria Rita; Adamo, Vincenzo; Esposito, Francesca; et al. (Frontiers in Endocrinology, 2023)
Lung neuroendocrine neoplasms (NENs) are rare malignancies developed from bronchial mucosa. Because of its rarity and complex histopathology, there is limited data on the role of chemotherapy in these subset of tumors. Few studies regarding the treatment of poorly differentiated lung NENs, known as neuroendocrine carcinomas (NECs), are available and many limits are detectable as heterogeneity of tumor samples including different origins and different clinical behaviors, moreover, no evidence of therapeutic advances have been achieved along the last thirty years. We performed a retrospective analysis of 70 patients affected by poorly differentiated lung NECs, evaluating the therapeutic efficacy of cisplatin/carboplatin plus etoposide scheme for the treatment of these patients. In our analysis, the outcomes of patients treated with either cisplatin or carboplatin schedule are similar in terms of ORR (44% versus 33%), DCR (75% versus 70%), PFS (6.0 versus 5.0 months) and OS (13.0 versus 10 months). Survival rate in our study suggests that high grade lung NENs are characterized by an aggressive behavior and a poor prognosis, despite the treatment with platinum/etoposide according to available data. Clinical results of present study contribute to strengthen available data on the usefulness of platinum/etoposide regimen in the treatment of poorly differentiated lung NECs